Peru : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Peru. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that Peru remains one of the best performing economies in Latin America, with solid macroeconomic policies and fundamentals and visible gains in poverty reduction. However, like most of the region, Peru faced a challenging external environment in 2014. Lower metal prices and weaker demand from trading partners were a major drag on private investment and exports. On the domestic front, an unexpected drop in subnational public investment level and temporary supply disruptions in mining, fishing, and agriculture compounded external shocks. Real GDP is projected to expand at about 3.75 percent in 2015, contingent on the reversal of the supply shocks and policy stimulus of 2014. Growth is expected to rise in 2016-17.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet